2012
DOI: 10.1189/jlb.0811443
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived matrix metalloproteinase-9 is a potent activator of trypsinogen in acinar cells in acute pancreatitis

Abstract: MMPs are generally considered to regulate degradation and remodeling of the ECM. Convincing data also implicate a role for MMPs in inflammatory conditions, such as AP, although the mechanisms are not known. The aim of this study was to define the role of MMPs in regulating activation of trypsinogen and tissue damage in AP, which was induced by infusion of taurocholate into the pancreatic duct in mice. A broad-spectrum MMP inhibitor (BB-94) and MMP-9 gene-deficient mice were used. Neutrophil secretions and rMMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
2
35
0
1
Order By: Relevance
“…Furthermore, infiltrating inflammatory cells (both neutrophils and macrophages) mediate the pathologic, intra-acinar activation of trypsinogen, which is a key feature of pancreatitis. 48,49,55,56 TNF α , 14,46,48 ROS (generated by neutrophil reduced nicotinamide adenine dinucleotide phosphate oxidase), 55 matrix metalloproteinase-9, 49 and p53 81 were proposed as mediators through which infiltrating inflammatory cells promote acinar cell death and trypsinogen activation. The persistent, low-grade inflammation also promotes pancreatic fibrosis by facilitating activation of stellate cells.…”
Section: Role Of Inflammation In Pancreatitismentioning
confidence: 99%
“…Furthermore, infiltrating inflammatory cells (both neutrophils and macrophages) mediate the pathologic, intra-acinar activation of trypsinogen, which is a key feature of pancreatitis. 48,49,55,56 TNF α , 14,46,48 ROS (generated by neutrophil reduced nicotinamide adenine dinucleotide phosphate oxidase), 55 matrix metalloproteinase-9, 49 and p53 81 were proposed as mediators through which infiltrating inflammatory cells promote acinar cell death and trypsinogen activation. The persistent, low-grade inflammation also promotes pancreatic fibrosis by facilitating activation of stellate cells.…”
Section: Role Of Inflammation In Pancreatitismentioning
confidence: 99%
“…It has been reported that neutrophil-derived reactive oxygen species (ROS) and enzymes, such as elastase and matrix metalloproteinase-9 (MMP-9) might contribute to neutrophil-mediated tissue damage in AP. 13,14 On top of those proposed mechanisms thus far, new aspects of neutrophil biology might help to explain how neutrophils cause tissue injury in the inflamed pancreas. Recent findings have demonstrated that activated neutrophils, beside secretion of antimicrobial compounds and phagocytic killing, can eliminate invading microorganisms by expelling nuclear DNA forming extracellular web-like structures decorated with nuclear histones as well as granular and cytoplasmic proteins.…”
Section: Introductionmentioning
confidence: 98%
“…The histological findings of experimental pancreatitis include cell necrosis and haemorrhage. Furthermore, an activation of trypsinogen to trypsin together with neutrophil infiltration occurs [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Activation of the serine protease inhibitors could theoretically increase the activity of serine proteases such as trypsin and chymotrypsin [17]. The role of MMP-9 and TIMP-1 have been extensively studied in AP and serum levels of MMP-9 have been found to be of possible prognostic significance [4, 18, 19, 20, 21]. In rodent AP models the pancreatic enzyme trypsin caused remarkable MMP-9 release [22], whereas inhibition of MMP-9 reduced trypsinogen activation [4].…”
Section: Introductionmentioning
confidence: 99%